AB0581 The Estimated Annual Incidence Rate of Polyarteritis Nodosa in Slovenia. (10th June 2014) - Jese, R.; Rotar, Z.; Praprotnik, S.; Hocevar, A.; Tomsic, M.
Abstract : Background: Polyarteritis nodosa (PAN) is a necrotising vasculitis of medium and small sized muscular arteries. It is a rare disease, with reported annual incidence rate of 1–8 cases per 10 6 adults. 1, 2 In areas where hepatitis B virus (HBV) infection is hyperendemic however, the annual incidence rate is much higher, i.e. up to 77 per 10 6 adults. 3 Objectives: To determine the annual incidence rate of PAN within a well-defined adult population of the Ljubljana region of Slovenia. Methods: A retrospective chart review of adult patients diagnosed with PAN was performed at the Department of Rheumatology of University Medical Centre Ljubljana, which is a part of an integrated secondary/tertiary university teaching hospital, that is the only referral rheumatology centre in the Ljubljana region, which represents about a quarter of Slovenian population. Potential cases were identified by searching the electronic medical records for ICD-10 codes M30.0. The electronic and paper records of patients who were residents of the Ljubljana region at the time of diagnosis were then thoroughly reviewed. Cases fulfilling the ACR 1990 classification criteria for PAN with either histologically proven vasculitis or characteristic arteriographic abnormalities were included in the analysis. The annual incidence rate of PAN was then calculated. Results: Between January 1, 2003 and December 31, 2012 (10 years of observation) five new cases (3 male, 2 female, male:female ratio=1, 5; median age 49 (range 27–72) years) of PAN were identified in the Ljubljana region with a population of 527, 000 aged 18 years or above. Patients' clinical characteristics at the time of diagnosis are presented in Table 1 . Four patients complained of myalgias and all male patients had testicular pain. Peripheral nerve lesions were identified in two. Three patients had arteriographic abnormalities; two of them had the characteristic microaneurysms. One patient had an active HBV infection. One had a localized cutaneous form of PAN on the basis of nodular skin changes with typical histological picture and no other organ system involvement (Case 1*). During the follow up one patient developed AA amyloidosis. Conclusions: The estimated annual incidence rate of PAN was 0.95 per 10 6 adults. References: Gonzalez-Gay, MA, et al. Arthrit Care Res, 2003, 49.3: 388-93. Watts, RA, et al. Arthritis Rheum, 2000, 43.2: 414-19. McMahon, BJ, et al. Hepatology, 1989, 9.1: 97-101. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2564